Epidemiology and public health importance of bovine salmonellosis - Abdulaziz M. ALMUZAINI; Ahmed I. ALAJAJI (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2025)
Bovine salmonellosis caused by Salmonella enterica subsp. enterica serovar Dublin (S. Dublin) is a significant public health and economic concern globally. It leads to severe health issues in cattle, including enteritis, septicaemia, and abortion, with high mortality rates, especially in newborn calves. The disease not only impacts the wellbeing of the animals but also results in substantial economic losses through treatment costs, reduced milk production, and potential outbreaks. The transmission of S. Dublin is primarily through contaminated food, water, and environmental exposure, with the faecal route being the most significant mode of spread. The pathogenesis of S. Dublin involves complex interactions between the bacteria and the host immune system, with the bacteria capable of persisting in the herd as carriers, further complicating control measures. Effective control strategies are critical to minimizing its spread, and understanding the epidemiology, clinical signs, and diagnostic methods is key. This review demonstrates the public health importance, clinical manifestations, economic importance and diagnostic techniques of bovine salmonellosis.